Moderasi Beragama Antara Komunitas Muhammadiyah dan Komunitas Islamiyah dalam Mewujudkan Nilai Keislaman di Desa Sialagundi - Syawaluddin Nst; Arina Risqi; Anju Minta Marito Manik; Wisuda Rohma Lubis; Janna Widya Limbong; Deliana Widya Rambe (MODELING: Jurnal Program Studi PGMI, 2023)
Moderation is an adjective derived from the word moderation, which means excess, middle or medium. This moderation can be interpreted not to homogenize religion, but to respond to religion with wisdom. The purpose of this paper is to discuss how the condition of the community in Sialagundi Village who coexist with different understandings in the teachings of the Islamic religion, but can realize each other's Islamic values in the midst of these differences in understanding. The method used in this study is literature research. It is concluded that religious moderation is actually the key to creating tolerance and harmony, both at the local, national, level, whereas in real-life real-life reality, human beings cannot avoid themselves from opposite matters. And it requires an attitude of religious moderation in the form of a tolerant attitude, and respect for dissent in religion. The people of Sialagundi Village who have two understandings between Muhammadiyah and Nahdlatul Ulama (NU) or what is often called Islamiyah by the local population. The two established a harmonious relationship through positive social interaction, by jointly trying to maintain Islamic values, ethics and sharia in each of their activities. Although different, these two communities live in harmony side by side while spreading Islamic values without coercion and excessive action.